Synthesis of Novel Angular Diazaphenoxazinone Derivatives via Palladium Catalyzed Buchwald-Hartwig Amidation Protocols - Odaa, M.E.; Okoro, U.C.; Ugwu, D.I. (Asian Journal of Chemistry, 2015)
The synthesis of new amido derivatives of angular diazaphenoxazinone via tandem amidation protocol is reported. This was achieved by the condensation of 4,5-diamino-6-hydroxypyrimidine (7) with 2,3-dichloro-1,4-naphthoquinone (8) in anhydrous basic medium to furnish the key intermediate, 11-amino-6-chloro-8,10-diazabenzo[a]phenoxazin-5-one (9). Palladium catalyzed amidation reaction of 11-amino-6-chloro-8,10-diazabenzo[a]phenoxazin-5-one (9) with different amides (12a-c) (benzamide, acetamide, salicylamide and 4-nitrobenzamide) in the presence of palladium(II) acetate, triphenyl phosphine (PPh3), water and tertiary butanol at 110 °C for 3 h gave the new amido derivatives 13a-c. Structures of the new compounds were established by elemental analysis, UV, FTIR, 1H NMR and 13C NMR.